Community Engagement in Academic Health Centers: A Model for Capturing and Advancing Our Successes - Karen Vitale; Gail L. Newton; Ana F. Abraido-Lanza; Alejandra N. Aguirre; Syed Ahmed; Sarah L. Esmond; Jill Evans; Sherril B. Gelmon; Camile Hart; Deborah Hendricks; Rhonda McClinton-Brown; Sharon Neu Young; et al. (The University of Alabama, 2022)
Academic health centers (AHCs) are under increased pressure to demonstrate the effectiveness of their community-engaged activities, but there are no common metrics for evaluating community engagement in AHCs. Eight AHCs piloted the Institutional Community Engagement Self-Assessment (ICESA), a two-phase project to assess community-engagement efforts. The first phase uses a framework developed by the University of Rochester Medical Center, which utilizes structure, process, and outcome criteria to map CE activities. The second phase uses the Community-Campus Partnerships for Health (CCPH) Self-Assessment to identify institutional resources for community engagement, and potential gaps, to inform community engagement goal-setting. The authors conducted a structured, directed content analysis to determine the effectiveness of using the two-phase process at the participating AHCs. The findings suggest that the ICESA project assisted AHCs in three key areas, and may provide a strategy for assessing community engagement in AHCs.